The factors affecting effectiveness of treatment in phages therapy - CHATAIN-LY, Mai Huong (Frontiers in Microbiology, 2014)
In recent years, the use of lytic bacteriophages as antimicrobial agents controlling pathogenic bacteria has appeared as a promising new alternative strategy in the face of growing antibiotic resistance which has caused problems in many fields including medicine, veterinary medicine and aquaculture. The use of bacteriophages has numerous advantages over traditional antimicrobials. The effectiveness of phage applications in fighting against pathogenic bacteria depends on several factors such as the bacteriophages/target bacteria ratio, the mode and moment of treatment, environmental conditions (pH, temperature ...), the neutralization of phage and accessibility to target bacteria, amongst others. This report presents these factors and the challenges involved in developing phage therapy applications